2011
DOI: 10.1097/ijg.0b013e3181efb065
|View full text |Cite
|
Sign up to set email alerts
|

The “ISN'T Rule” in Healthy Participant Optic Nerve Head by Confocal Scanning Laser Ophthalmoscopy

Abstract: In healthy participants the rim shape as measured by the HRT did not follow the ISN'T rule, except that the smallest rim part was located in the temporal disc region. The thickness of the rim was similar in the superior and the inferior sectors by HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…This is supported by other studies that also found that the temporal quadrant had the largest rim area in only 0% 11 to 1% 6 of normal eyes. The mean temporal rim area was significantly less than the mean rim area of all other quadrants, as previously suggested by Iester et al 3 The thinnest rim area being in the temporal quadrant, therefore, seems to be a quality shared by most normative eyes. Our study suggests that compliance to this rule was independent of disc area but not age.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is supported by other studies that also found that the temporal quadrant had the largest rim area in only 0% 11 to 1% 6 of normal eyes. The mean temporal rim area was significantly less than the mean rim area of all other quadrants, as previously suggested by Iester et al 3 The thinnest rim area being in the temporal quadrant, therefore, seems to be a quality shared by most normative eyes. Our study suggests that compliance to this rule was independent of disc area but not age.…”
Section: Discussionsupporting
confidence: 69%
“…2 Recent studies assessing the ISNT rule fulfillment by Heidelberg Retina Tomograph (HRT) have had varying results (12% to 56% fulfillment). [3][4][5] This has led to interest in alternative rules such as IS (I > S) and IST (I > S > T) rules, which have fulfillment rates of 56% to 93% 2,3,5-8 and 71%, 5 respectively. In addition, given the variability of ISNT rule fulfillment, understanding factors associated with ISNT rule violation would be clinically relevant.…”
mentioning
confidence: 99%
“…However, in this study, we chose to investigate quantitative OCT RNFL thickness measurements, because it is the most commonly used and reported parameter in OCT for glaucoma. 24 Other alternative studies have also investigated the applicability of the ISNT rule using CSLO measured neuroretinal rim parameters such as the rim area 18, 21, 22 and rim volume. 22 In general, the validity of the ISNT rule for these rim parameters were also reported to be very low (10.7% – 18%) 21, 22 but was also considerably higher for the IST and IS rule (53.3% – 77%).…”
Section: Discussionmentioning
confidence: 99%
“…24 Other alternative studies have also investigated the applicability of the ISNT rule using CSLO measured neuroretinal rim parameters such as the rim area 18, 21, 22 and rim volume. 22 In general, the validity of the ISNT rule for these rim parameters were also reported to be very low (10.7% – 18%) 21, 22 but was also considerably higher for the IST and IS rule (53.3% – 77%). 18, 21, 22 However, further investigation is needed to determine whether OCT derived neuroretinal rim parameters comply better with the ISNT rule compared to CSLO rim parameters.…”
Section: Discussionmentioning
confidence: 99%
“…5 Exclusion of the nasal rim from morphometric disc analysis has been suggested because this quadrant is usually the last to be affected in glaucoma and the borders of the optic cup in this sector are difficult to identify because of the presence of large retinal veins. 6,7 As the most common feature examined is the relative width of the inferior, the superior, and the temporal rims, the "IST" rule was defined, wherein the inferior quadrant is thicker than the superior quadrant, which in turn is thicker than the temporal quadrant. In addition, the "T" rule was described, which was defined to hold true if the temporal quadrant measurements were less than the other 3 quadrants.…”
mentioning
confidence: 99%